Egg freezing for fertility preservation and family planning: a nationwide survey of US Obstetrics and Gynecology residents - Navid Esfandiari; Julia Litzky; Joshua Sayler; Pavel Zagadailov; Karen George; Leslie DeMars (BMC, 2019)
Abstract Background Little is known about resident attitudes toward elective egg freezing (EF) or how educational exposure to EF affects residents' views and ability to counsel patients. This study aimed to evaluate US OB/GYN residents' views on elective EF, decisions regarding family planning, and whether education on EF affects these views and self-reported comfort discussing EF with patients. Methods A 32 question survey was emailed to program directors at all US residency programs for distribution to residents. Chi-square tests were used to evaluate the relationship between educational factors and views on EF and comfort counselling patients. Results Of those surveyed, 106 residents and 7 fellows completed the survey (103 female). Almost three quarters of female respondents reported postponing pregnancy due to residency (71.8%). Non-exclusive reasons for this choice included career plans (54.4%) and concern for childcare (51.5%) and for fellow residents and their program (50.5%). Of the male and female residents who reported educational exposure to EF (57.5%), almost all of them (95.4%) received this in an REI rotation. Only half of female residents reported being comfortable counseling a patient on EF (49.5%). For female residents, education on EF (p = 0.03) and more advanced level of residency (p = 0.02) were significantly associated with comfort counseling a patient on EF. Conclusions Female OB/GYN residents are choosing to delay pregnancy during residency for career and social support reasons. Few residents feel comfortable counseling patients on EF, but appropriate curricular content on EF during residency could improve residents' comfort in assisting patients with reproductive planning.